2020
DOI: 10.1002/mats.202000060
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of a Viscous Fluid Flowing through an External Gear Pump

Abstract: Gear pumps are frequently used for the transport of high‐viscosity fluids, for instance, for the extrusion of polymers. The flow rate of this extrusion process is regularly controlled by an external gear pump. In this work, the 2D flow of a viscous fluid through such an external gear pump is studied using the finite element method. Local mesh refinement based on the respective distance between moving boundaries is essential to capture the relatively narrow clearances in the pump. The gear pump works against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 36 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…The meshing procedure for this 2D mesh is based on the work of Mitrias et al [39] and is discussed in earlier work of the authors. [33] In principle, the local element size is determined by the respective distance between boundaries. This mesh is extruded in the third direction, (b), resulting in a mesh with prism elements.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The meshing procedure for this 2D mesh is based on the work of Mitrias et al [39] and is discussed in earlier work of the authors. [33] In principle, the local element size is determined by the respective distance between boundaries. This mesh is extruded in the third direction, (b), resulting in a mesh with prism elements.…”
Section: Methodsmentioning
confidence: 99%
“…The drop in efficiency is faster, that is, in a smaller range of the Hersey number for more shear-thinning fluids. Next to the pump curves, our previous study [33] showed zones with a high residence time in the inflow channel of the external gear pump. In external gear pumps, an axial clearance is present besides the previously studied radial clearance.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations